1998
DOI: 10.1002/(sici)1097-4644(19980901)70:3<366::aid-jcb10>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative interactions between MEF-2 and Sp1 in muscle-specific gene regulation

Abstract: Previous investigations have demonstrated synergistic interactions in vivo between CCAC and A/T-rich nucleotide sequence motifs as functional components of muscle-specific transcriptional enhancers. Using CCAC and A/T-rich elements from the myoglobin and muscle creatine kinase (MCK) gene enhancers, Sp1 and myocyte-specific enhancer factor-2 (MEF-2) were identified as cognate binding proteins that recognize these sites. Physical interactions between Sp1 and MEF-2 were demonstrated by immunological detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Interestingly, according to the model, the intersite distance for the site pair Mef2-Myf is distributed according to the helical phasing distribution, which was also observed in (25). The other observed interactions are also supported by the literature or TransCompel: Tef-Mef2 (40), Myf-Sp1 (36) and Mef2-Sp1 (41). …”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, according to the model, the intersite distance for the site pair Mef2-Myf is distributed according to the helical phasing distribution, which was also observed in (25). The other observed interactions are also supported by the literature or TransCompel: Tef-Mef2 (40), Myf-Sp1 (36) and Mef2-Sp1 (41). …”
Section: Discussionsupporting
confidence: 79%
“…This functional crosstalk has been molecularly explained by a direct interaction between the myogenic bHLH/E12 heterodimers with SRF (Groisman et al, 1996). Similarly, Sp1 associates with myogenic bHLH (Biesiada et al, 1999) and MEF2 (Grayson et al, 1998) proteins, and Sp-1 sites are frequently found to be necessary for activation of muscle gene expression (Gustafson and Kedes, 1989;Sartorelli et al, 1990). Consistent with their positive role in muscle gene expression, myogenic bHLH, SRF, and Sp1 are found on a muscle-specific transcriptional complex (Biesiada et al, 1999).…”
Section: Positive Regulators Of Myogenesismentioning
confidence: 81%
“…Relationships between the enzymatic activity of calcineurin in hindlimb muscles and expression of myoglobin and troponin I slow, endogenous genes known to be controlled by MEF2 activity (Grayson et al ., 1998; Wu et al ., 2000; Yan et al ., 2001) and induced by exercise or motor nerve stimulation (Underwood and Williams, 1987) were assessed by the comparison of five independent lines of transgenic mice engineered to express a constitutively active form of calcineurin under the control of the MCK promoter. Three different transgene constructions were used, as shown in Figure 6A.…”
Section: Resultsmentioning
confidence: 99%